Clinical Efficacy of Diltiazem in Hyperthyroidism - Marwat, Mushtaq Ahmad; Javaid, Farooq; Rauf, Muhammad; Shah, Shoaib; Nawab, Gul (Journal of Postgraduate Medical Institute, 2011)
To evaluate the effect of diltiazem on the adrenergic manifestations of hyperthtyroidism. This prospective interventional study included newly diagnosed patients with untreated hyperthyroidism attending the out patient department of IRNUM Peshawar. All patients took Diltiazem 30mg three times a day for 6 weeks. Clinical assessment was done before starting therapy and then serially after 1,2,4 and 6 weeks (+3days) using standardized and modified hyperthyroid symtpoms score (HSS) including excessive sweating, trembling hands, heat intoleranc, easy fatigability, nervousness, diarrhoea, increased appetitie, palpitation and dyspnoea on exertion. Diltiazem effictively controls the clinical manifestations of hyperthyroidism.